Comparing Tax and Tax Reallocations Payments in Financing Rail Noise Abatement Programs: Results from a CE valuation study in Italy - Paulo A.L.D. Nunes; Chiara M. Travisi (Fondazione Eni Enrico Mattei (FEEM), 2006)
The paper examines the use of choice experiments (CE) to assess the economic value of alternative rail noise reduction interventions on the so-called Brennero railway, Italy. The novelty of this paper is threefold. To our knowledge, this is the first study on the valuation of noise conducted in Italy and it is the first example of CE applied in the field of rail noise valuation. Second, we consider not only the economic value assessment of noise reduction but also how this reduction is achieved, ranging from policy instruments such as barriers or train technology. Third, the paper provides an original contribution in the valuation literature since we test formally the econometric robustness of the CE estimates under three payment vehicles. In fact, we consider (a) a special regional tax, (b) reallocation of financial resource within the provincial budget on the public transport sector, and (c) reallocation of financial resource of the provincial budget from the administration and entertainment sector. Test results are mixed. Welfare analysis and policy implications of valuing rail noise reduction programs using different payment vehicles are discussed.
Keywords: C0; R41; 330; Choice Experiment; Noise Abatement; Tax; Tax Reallocation; Formal Testing; Welfare Analysis; Lärmschutz; Schienenverkehr; Hedonischer Preisindex; Wohlfahrtsanalyse; Italien